Development and Validation of Predictors for the Survival of Patients With COVID-19 Based on Machine Learning - Zhao, Yongfeng; Chen, Qianjun; Liu, Tao; Luo, Ping; Zhou, Yi; Liu, Minghui; Xiong, Bei; Zhou, Fuling (Frontiers in Medicine, 2021)
Background. The outbreak of COVID-19 had attracted the attention of the whole world. Our study aimed to explore the predictors for the survival of patients with COVID-19 by machine learning. Methods. We conducted a retrospective analysis and used the idea of machine learning to train the data of COVID-19 patients in Leishenshan Hospital through the logical regression algorithm provided by scikit-learn. Results. Of 2010 patients, 42 deaths were recorded until March 29th, 2020. The mortality rate was 2.09%. There were 6812 records after data features combination and data arrangement, 3025 records with high-quality after deleting incomplete data by manual checking, 5738 records after data balancing finally by the method of Borderline-1 Smote. The results of ten times of data training by logistic regression model showed that albumin, saturation of pulse oxygen at admission, alanine aminotransferase and percentage of neutrophils were possibly associated with the survival of patients. The results of ten times of data training including age, sex, and height beyond the laboratory measurements showed that percentage of neutrophils, saturation of pulse oxygen at admission, alanine aminotransferase, sex and albumin were possibly associated with the survival of patients. The rates of precision, recall and f1-score of the two training models were all higher than 0.9, and relatively stable. Conclusions. We demonstrated that percentage of neutrophils, saturation of pulse oxygen at admission, alanine aminotransferase, sex and albumin were possibly associated with the survival of patients with COVID-19.